Constructive Skepticism and Being a Mirror in the Zhuangzi. Issue 1 (30th December 2018) - Wong, David B.
Abstract: The Zhuangzi text deploys two epistemic themes to accomplish its ends of combatting human pretensions to know the world and to prompting us to rediscover the world through fresh eyes. To get us to shed our arrogant dispositions it applies a constructive skepticism to whatever it is that human beings claim to know. To point towards a more constructive relationship with Nature, it articulates the stance of being a mirror to nature. This essay will explain how the text does this and relates its conceptions of skepticism and being as mirror to relevant contemporary science.